Stressful life experiences, alcohol consumption, and alcohol use disorders: the epidemiologic evidence for four main types of stressors - Keyes, Katherine M. (2011)
BACKGROUND: Exposure to stress is potentially important in the pathway to alcohol use and alcohol use disorders. Stressors occur at multiple time points across the life course, with varying degrees of chronicity and severity. METHOD: We review evidence from epidemiologic studies on the relationship between four different stressors (fateful/catastrophic events, child maltreatment, common adult stressful life events in interpersonal, occupational, financial, and legal domains, and minority stress) and alcohol consumption and alcohol use disorders. RESULTS: Studies generally demonstrate an increase in alcohol consumption in response to exposure to terrorism or other disasters. Research has demonstrated little increase in incident alcohol use disorders, but individuals with a history of alcohol use disorders are more likely to report drinking to cope with the traumatic event. Childhood maltreatment is a consistent risk factor for early onset of drinking in adolescence and adult alcohol use disorders, and accumulating evidence suggests that specific polymorphisms may interact with child maltreatment to increase risk for alcohol consumption and disorder. Stressful life events such as divorce and job loss increase the risk of alcohol disorders, but epidemiologic consensus on the specificity of these associations across gender has not been reached. Finally, both perceptions of discrimination and objective indicators of discrimination are associated with alcohol use and alcohol use disorders among racial/ethnic and sexual minorities. CONCLUSION: Taken together, these literatures demonstrate that exposure to stress is an important component in individual differences in risk for alcohol consumption and alcohol use disorders. However, many areas of this research remain to be studied, including greater attention to the role of various stressors in the course of alcohol use disorders and potential risk moderators when individuals are exposed to stressors.